Menganalisis Kelengkapan Organisasi dan Permodalan Koprasi Terhadap Sistem Koprasi - Iqbal Maulana; Muhammad Yasin (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Cooperatives are business entities based on family principles and aim to improve the welfare of members. Organizational and capital completeness are two important factors that determine the effectiveness of cooperatives in achieving their goals. Organizational completeness refers to the structure and governance of a good cooperative, including the existence of an optimally functioning board, supervisor, and member meeting. This research uses a qualitative method. The results of this study reveal that a complete cooperative organization is the key to success in running a cooperative system. In addition to having complete administrators, supervisors, and member meetings, cooperatives also need to have a strong institutional structure. In addition, in terms of capital, having sufficient sources of funds will enable the cooperative to develop its business, expand its range of services, and have financial resilience in the face of risks that may arise. Thus, the overall comprehensiveness of the cooperative's organization and capital will be instrumental in determining the success of the cooperative system. Both aspects support each other to create an operational environment that is stable, transparent, and able to respond to challenges and opportunities in the market.